MENINGKATKAN DASAR PEMAHAMAN UMAT BERAGAMA HINDU MELALUI AJARAN KONSEP PANCA SRADHA DALAM LONTAR TUTUR KUMARA TATTWA - I Nyoma Ariyoga (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2019)
The Hindu community is actually very rich in literary works such as geguritan, kidung, kekawin, stories, and lontar which are inherited from ancestors that need to be preserved. Hinduism has always been a source of inspiration that inspired many traditional texts owned by people in Bali, one of which was Lontar Tutur Kumara Tattwa. Lontar Tutur Kumara Tattwa is one of thousands of manuscripts inherited by Balinese today. Growing understanding of Hinduism cannot always be learned from a tradition that lives and develops in the midst of society. Moreover, to improve the understanding of Hinduism in this post-modern era, it is more conducive to resynergize the teachings that are excellent in lontar texts with religious activities so that they are not out of their way. Lontar Tutur Kumara Tattwa can be the basis for understanding Hindu religious activities and being a mental foundation for acting in society. As it is known that attachment to worldly things causes someone to forget his essence, so that the suffering experienced from the reflection of attachment causes a person to blame the situation and get lost in the niche of suffering. Religion is a way that can be done to end suffering, as in Lontar Tutur Kumara Tattwa contains philosophical teachings about why humans suffer and how humans escape from suffering. Suffering can be stopped one of them by increasing the belief (sradha) and deep understanding of the teachings of the concept of Panca Sradha which consists of Widhi Sradha, Atma Sradha, Karma Phala Sradha, Punarbhawa Sradha, and Moksa Sradha. Keywords: Understanding of Hinduism, Panca Sradha, Lontar Tutur Kumara Tattwa